IMPLEMENTASI E-GOVERNMENT DALAM PEMERINTAHAN KECAMATAN SEDAYU “SEDAYU SMART DISTRIC” - Ardiyati (Journal Publicuho, 2022)
The research have a purpose to analyze the implementation of e-government policies in Sedayu District government in the concept of "Sedayu Smart District". The study used a qualitative descriptive method by intering various government stakeholders in Sedayu District and the Communication and Information Agency of Bantul Regency. The research was also carried out by searching primary documents in the form of Sedayu sub-district government documents, and secondary documents in the form of news in various media. The study found that the implementation of Sedayu Smart District in the concept of "Jagoriko" was poorly planned, lacked coordination, lacked monitoring and evaluation. Implementation of policies is less institutionalized and dependent on the leadership so that it is less sustainable. The lack of policy implementation has led to the grand design of Bantul Smart City which refers to the 6 pillars of the target of e-government development in local government. Improvements need to be made in planning, coordinating, implementing, monitoring and evaluating Sedayu Smart District policies in order to remain sustainable. The concept of e-government in the administration of sub-district government in Bantul Regency is an innovation of each regional government organization